Year-End Tax Planning of Top Management: Evidence from High-Frequency Payroll Data - Kreiner, Claus Thustrup; Leth-Petersen, Søren; Skov, Peer Ebbesen (American Economic Review, 2014)
Using Danish high-frequency payroll data and tax reform variation, we detect year-end tax avoidance among top managers. Five to seven percent of top managers exploit year-end tax planning strategies to save taxes. Around 30 percent of the top managers engaging in year-end tax avoidance do so by retiming bonus payments while the rest shift regular wage income. However, bonus timing is most tax-sensitive. When considering all of the top managers receiving a December bonus, we find that more than one-quarter retime the bonus payment, whereas only 5 percent of those not receiving a bonus shift regular wage income.